Implementing european law principles in the framework of transformations of the relationships between national legal systems and EU law: Reflections on the Ruling of the Italian Constitutional Court No. 181/2024 - Acocella, Carla (P.A. Persona e Amministrazione, 2025)
The Paper aims to analyze the issue of implementing European law principles within the national legal systems, as a phenomenon related to the expansion of the fields of European action. This expansive trend produces a transformation of the coordinates within which the dialogue between the European and national legal systems is placed, in particular with regard to the impact of the Charter of Fundamental Rights of the EU (directly applicable and therefore cause of expansion of the area of possible conflicts with domestic law), the growing protection of the fundamental rights of European citizens, and the tendency to formalize European Law Principles in primary European law with their express provision in the treaties and with the attribution to them, to many of them, of a constitutional value. In this context the judgement of the Italian constitutional Court n. 181/2024 fits in. The paper will move from its reasoning in order to show the interaction between all this issues, that are not lying on the ground of the dialogue between legislators (European and national) and judges, but highlight the need to refer the implementing dimension of European law principles to the dialogue between administration and national (common) judges. According to the ruling’s reasoning, the inadequacy of the disapplication tool in order to effectively defend the primacy of European law would arise, among others, precisely in the cases where public administration continues to apply uncertain and controversial provisions. On the other hand, the judgement deals with one of the general principles, namely the non-discrimination principle, which appears as a paradigmatic field of analyses of issues such as those here mentioned.